An Analysis of Reading Comprehension Difficulties in TOEFL Test By High School Students - Anita Lovia Girsang; Fransiska Vanny Guitara Marbun; Yusri Apriani Margaretha Turnip; Erikson Saragih (Linguistic, English Education and Art (LEEA) Journal, 2019)
This research was conducted with the aim of finding out the difficulties that were felt by high students in answering reading comprehension questions on the TOEFL test.The method used in this research is qualitative method. This research was conducted on high school students who had taken the TOEFL test. From the results of this study it was found that the biggest problem in reading comprehension in the TOEFL test was due to the lack of interest in reading high school students so they would feel bored by seeing the text in front of them and it was still difficult for high school students to find the meaning of the text due to lack of vocabulary, and lack of practice to answer questions related to reading comprehension with the lack of practice, they think that the time to answer questions is not enough. So from the research conducted it is expected to overcome these difficulties, high school students must increase their practice of reading comprehension questions both at home and at the course, and must increase interest in reading and increase vocabulary so that it is easier to work on problems in the reading comprehension section. Keywords: reading comprehension,TOEFL